2015
DOI: 10.3109/00365548.2015.1007476
|View full text |Cite
|
Sign up to set email alerts
|

Absence ofStreptococcus pneumoniaein pharyngeal swabs of geriatric inpatients

Abstract: Colonization of the pharynx by Streptococcus pneumoniae was studied in 185 in-hospital geriatric patients (median age 81 years) from 29 March 2011 to 22 June 2011. Swabs were plated on blood agar plates. Colonies with a morphology suggesting S. pneumoniae were further analyzed. Surprisingly, pneumococci were not found in any of the samples. Pneumococci chronically colonizing the pharynx of elderly people may be much rarer than previously thought and probably are not the source of pneumococcal pneumonia in old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…With a post-serotyping prevalence of 0.8%, we found a quite lower pneumococcal carriage rate than expected [ 13 , 20 , 21 ]. However, our study confirmed the results of recent studies in seniors [ 22 24 ], nursing home residents [ 23 ] and geriatric patients [ 25 ] revealing carriage rates between 0% and 2.3%. To improve detection of pneumococcal carriage, we used nasopharyngeal and oropharyngeal swabs as previously suggested [ 26 ] taken by a specifically trained study nurse [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…With a post-serotyping prevalence of 0.8%, we found a quite lower pneumococcal carriage rate than expected [ 13 , 20 , 21 ]. However, our study confirmed the results of recent studies in seniors [ 22 24 ], nursing home residents [ 23 ] and geriatric patients [ 25 ] revealing carriage rates between 0% and 2.3%. To improve detection of pneumococcal carriage, we used nasopharyngeal and oropharyngeal swabs as previously suggested [ 26 ] taken by a specifically trained study nurse [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, colonization rates strongly depend on sampling site, preanalytic conditions, processing methods (cultural or molecular detection by PCR) and age. Hence, colonization rates in elderly individuals can range from 0% [49] to 22% [19]. There is no clear evidence from the data available which sampling site yields optimal detection rates in adults.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study results, PCV13 covers 20% of the serotypes isolated. In similar studies from Europe, the coverage of PCV13 varied between 9.1% and 51.4% (16,19,20,22,23). In a recent study from Japan, 18.2% of the participants carried a pneumococcal serotype included in PCV13 (24).…”
Section: Discussionmentioning
confidence: 95%
“…Molecular methods to investigate NP pneumococcal carriage have been recently developed. Recent studies report that conventional culture methods underestimate pneumococcal carriage prevalence and molecular methods are superior to conventional methods in detecting pneumococcal carriage ( 19 , 20 , 22 , 23 , 24 ). Because of the lack of specific anti-sera for further serotyping in pneumotest plus kit, the serotypes of serogroup 10, 11, 15, 17, and 33 could not be determined and the exact vaccine coverage of PPSV23 could not be found.…”
Section: Discussionmentioning
confidence: 99%